Effect of Service Quality on Customer Satisfaction at BMT Mandiri Sejahtera, Sekapuk Branch - Dhita Dhora Damayanti (Jurnal Mantik, 2020)
The purpose of this study was to determine whether there is an influence of service quality on customer satisfaction at the Mandiri Sejahtera BMT Sekapuk Branch. The sample of this research was 60 BMT Mandiri Sejahtera Branch Customers in Sekapuk, sampling using a random sampling method that is determining the sample that provides equal opportunity for each member of the population to be sampled. Data analysis using Multiple Linear Regression Test with the accuracy of the model (classic assumption test), hypothesis testing using the coefficient of determination test (R2), persial test (t test), while processing data using SPSS 20. The results showed that the quality of service explains its existence against variables customer loyalty, besides that, service quality has a positive and significant impact on customer satisfaction.